Do Holistic Human Resource Management Practices Make a Difference to Fly-in Fly-out Workers’ Job Quality? An Exploratory Investigation - Connell, Julia; Burgess, John (National Institute of Labour Studies Inc., 2014)
In common with ongoing research into human resource management (HRM), there are attributes of jobs that are associated with job quality, which are considered important in attracting and retaining employees. To date, however, analysis has omitted the fly-in fly-out (FIFO) workforce. It is important to consider whether it is possible to develop a strategic HRM approach for FIFO workers where commuting arrangements deviate from the norm. This article fills a gap in the literature by using a four-dimensional job-quality (JO) framework to analyse factors associated with job quality and HRM. The research was undertaken at two FIFO-dependent workplaces in Western Australia. The findings show that one workplace was using bundles of HR practices that spanned all four JO dimensions; the other concentrated mainly on two dimensions, a consequence which is the potential to lead to suboptimal outcomes for the organisation and their FIFO employees.